Application of the Demonstration Learning Model to Improve Student Learning Outcomes in Class 4 Social Sciences Lessons at State Elementary School 15 Serang - Junaesih, Junaesih; Kurniawati, Ajeng; Humairoh, Humairoh (Jurnal Primagraha, 2022)
This research discusses the implementation of the demonstration method to improve student learning outcomes. Library research method with a qualitative descriptive approach. The results of this research from several theses and journals show that the demonstration method can improve student learning outcomes. Demonstration is a mode of presenting lessons by demonstrating and demonstrating to students a particular process, situation or object, either actually or just an imitation. The purpose of teaching using the demonstration model is a way of presenting lessons by demonstrating and demonstrating a process in front of students. The demonstration model is a way of presenting lessons by demonstrating and demonstrating a process in front of students.